Keterampilan Psikologis untuk Meningkatkan Efikasi Diri pada Pengguna Napza di Panti Rehabilitasi - Mutiara D N I (JIP (Jurnal Intervensi Psikologi), 2010)
Most drug abusers in rehabilitation house has low self efficacy which is seen on negative self concept, low self recognizing, and low self confidence.This lowseif efficacy may cause relapse among them. This research was aimed at seeing influence of psychological skill training on self efficacy among drug abusers in rehabilitation house. The Hypothesis of this research was there is a different increase of self efficacy between experiment group who got psychological skill training and control group who did not get psychological skill training. Participant of this research is drug abuser in rehabilitation house X in regular class. This research was experimental research with 6 participants in experiment group and 5 participants in control group which was divided randomly. The Design of this research was pre post control group design. Participant's self efficacy was measured by self efficacy scale. Statistics analysis using non parametric test, shows score z--2,470 and p=0,013 where 0,013 < 0, 05. Thus, hypothesis on this research is accepted.Keywords: Psychological skill, self efficacy, drug abusers